Forming reproducible non-lithographic nanocontacts to assess the effect of contact compressive strain in nanomaterials - Alex Lord (Semiconductor Science and Technology, 2015)
The application of electrical nanoprobes to measure and characterize nanomaterials has become widely spread. However, the formation of quality electrical contacts using metallic probes on nanostructures has not been directly assessed. We investigate here the electrical behaviour of non-lithographically formed contacts to ZnO nanowires (NWs) and develop a method to reproducibly form Ohmic contacts for accurate electrical measurement of the nanostructures. The contacting method used in this work relies on an electrical feedback mechanism to determine the point of contact to the individual NWs, ensuring minimal compressive strain at the contact. This developed method is compared with the standard tip deflection contacting technique and shows a significant improvement in reproducibility. The effect of excessive compressive strain at the contact was investigated, with a change from rectifying to ohmic I–V behaviour observed as compressive strain at the contact was increased, leading to irreversible changes to the electrical properties of the NW. This work provides an ideal method for forming reproducible non-lithographic nanocontacts to a multitude of nanomaterials.